Josef Ignaz Mildorfer 1719-1775 Akademieprofessor und Savoyisch-Liechtensteinischer Hofmaler - Leube-Payer, Elisabeth (2011)
This monograph on Joseph Ignaz Mildorfer (1719-1775) consists of forteen chapters, that after having given an overall curriculum, depict the various stations in the painter's working process. Special emphasis has been given to such criteria as the socio-economic, political and esthetic impacts, that shaped the development of this intriguing artist. Mildorfer was born into a distinguished family of painters in Innsbruck, where he was taught the basics of his profession. However, he was also exposed to the newly imported paintings from southern Germany, which at this time sparked Tyrolian tradition with international flavor. Partly due to those early stimuli, the young painter managed to instantly gain the renowned "big prize" of the Academy, upon his arrival in Imperial Vienna. This distinction was a prerequisite to any further career. Praised by his contemporaries as the most prodigious pupil of Paul Troger, Mildorfer soon was offered remarkable employments. His first major task, the complete decoration of the pilgrimage church at Hafnerberg near Vienna, comprising works in fresco and oil was soon to be followed by a commission from the Imperial court. But Austria was plagued by a raging War of Succession, which cast its shadow upon the job market, forcing Mildorfer to venture out into alternative fields. This he found in the painting of battlescenes. In this genre the young artist produced works of such rebellious intenseness that surpassed all his colleagues' endeavors and saved him a special niche. It might well be that those particular paintings drew the attention of the last great sponsers of the monarchy to Mildorfer, resulting in his being appointed painter of the court to the Duchess of Savoy, neé Maria Theresia Princess of Liechtenstein. (By way of scholarly work in the Princely Archives of Liechtenstein we have now established answers to questions regarding character and extend of Mildorfers work for the Duchess, that up till now has been obscured). In addition this period marked the beginning of a long lasting relationship with various branches of the Esterházy family, culminating in Mildorfer's appointment to Esterháza. Here he was commissioned to paint al fresco in Duke Nikolaus Esterházy's castle, one of the last manifestations of feudal style, the elaborate adornment of which promted the Duke with the attribute "The Magnificent". When Mildorfer was elected Professor at the Academy (kaiserlich-königliche Hofakademie der Mahler, Bildhauer und Baukunst) this not only marked the zenith of his career but also had major impact on one of the most thrilling phenomena within eighteenth century Viennese art. It was under his leadership that a movement took center stage, that was aprostophized the "Einheitsstil der Wiener Akademie". Carried out by an array of his scholars, notably Franz Anton Maubertsch this faszinating manifestation had Mildorfer's ideas at its core. With his contributions in the Crown Lands of the Habsburg monarchy in mind, his work makes him a typical Central-European artist of the eighteenth century. However some of his lesser graspable traits can only be understood out of the "Zeitgeist" and must be explained under the term of "painter of the sensibility". Since Mildorfer is the link between Paul Troger, his teacher and Franz Anton Maulbertsch, his student, a comprehensive biography of this artist is an absolute must. Only that makes a profound understanding of the third generation of Austrian barock-painting possible.